2021
DOI: 10.3386/w28455
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Does In-Person Schooling Contribute to the Spread of COVID-19? Evidence from Michigan and Washington

Abstract: for providing valuable feedback on this work at various points along the way. Any errors are our own. In addition, all opinions expressed in this paper are those of the authors and do not necessarily reflect the views of our institutions or funders, nor do they necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Existing empirical studies that have examined the impact of school reopenings or closures are limited and have generally found mixed results. A study by Goldhaber et al (2021) uses data from Michigan and Washington to examine changes in county-level COVID-19 case rates due to in-person schooling. The authors use a variety of ordinary least squares specifications that include school district or county fixed effects.…”
Section: Background On School-related Covid-19 Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing empirical studies that have examined the impact of school reopenings or closures are limited and have generally found mixed results. A study by Goldhaber et al (2021) uses data from Michigan and Washington to examine changes in county-level COVID-19 case rates due to in-person schooling. The authors use a variety of ordinary least squares specifications that include school district or county fixed effects.…”
Section: Background On School-related Covid-19 Transmissionmentioning
confidence: 99%
“…To date there is no national database of in-person school attendance rates, community testing, and case rates (Oster 2021). There is also no national database on the mitigation strategies employed by schools and school districts (Goldhaber et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This paper adds to the growing scientific consensus that at least some forms of in-person K-12 instruction have not contributed significantly to the spread of the pandemic, including all four of the studies using data from Fall 2020 that we cited above (Falk et al, 2021;Goldhaber et al, 2020;Harris et al 2021;Hobbs et al, 2020). There is still uncertainty, however, about the specific circumstances under which in-person K-12 instruction can safely be conducted.…”
Section: Discussionmentioning
confidence: 89%
“…There is still uncertainty, however, about the specific circumstances under which in-person K-12 instruction can safely be conducted. The CDC has continued to recommend that decisions about instruction types should depend on the level of transmission in the community (CDC, 2021) and two of those four prior studies suggested that in-person schooling may contribute more to the spread of the pandemic in communities with higher baseline levels (Goldhaber et al, 2020;Harris et al, 2021). Under the CDC's recommendations, as of March 2021, only four percent of children in the United States lived in counties with transmission levels low enough for full-time in-person learning (Keefe, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation